2019
DOI: 10.1080/09658211.2019.1661494
|View full text |Cite
|
Sign up to set email alerts
|

A positive Living-in-History effect: the case of the fall of the Berlin Wall

Abstract: Research has shown that individuals use a combination of cultural life script events and historical events when dating personal memories, providing evidence for a cultural life script effect and Living-in-History (LiH) effect on the temporal organization of autobiographical memory. Yet, in contrast to life script events, the LiH effect has only been found for negative events such as war or natural disasters. Therefore, this study tested whether a positive historical event, here the fall of the Berlin Fall, als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 44 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…Prior research has demonstrated that script-consistent and script-divergent events organize autobiographical memory and spawn memorable experiences. As noted in the introduction, both types of events serve as temporal landmarks (e.g., Bohn and Habermas, 2016;Shi and Brown, 2016;Gu et al, 2017;Camia et al, 2019), can give rise to "bumps" in the temporal distributions of recalled events (e.g., Pillemer et al, 1986Pillemer et al, , 1988Kurbat et al, 1998;Thomsen and Berntsen, 2005;Uzer and Brown, 2015;Brown et al, 2016;Shi and Brown, 2016;Gu et al, 2017;Thomsen et al, 2021) and are mentioned when people narrate their life stories (Glück and Bluck, 2007;Thomsen and Berntsen, 2008;Rubin et al, 2009;Bohn, 2010;Haque and Hasking, 2010;Dickson et al, 2011;Thomsen et al, 2011;Gu et al, 2017Gu et al, , 2019 and when adult children recall their parents' lives (Svob and Brown, 2012;Svob et al, 2016;Gu et al, 2019). Transition Theory (Brown et al, 2012(Brown et al, , 2016Brown, 2016Brown, , 2021 contends that these phenomena reflect the degree of change engendered by the transitions in question.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has demonstrated that script-consistent and script-divergent events organize autobiographical memory and spawn memorable experiences. As noted in the introduction, both types of events serve as temporal landmarks (e.g., Bohn and Habermas, 2016;Shi and Brown, 2016;Gu et al, 2017;Camia et al, 2019), can give rise to "bumps" in the temporal distributions of recalled events (e.g., Pillemer et al, 1986Pillemer et al, , 1988Kurbat et al, 1998;Thomsen and Berntsen, 2005;Uzer and Brown, 2015;Brown et al, 2016;Shi and Brown, 2016;Gu et al, 2017;Thomsen et al, 2021) and are mentioned when people narrate their life stories (Glück and Bluck, 2007;Thomsen and Berntsen, 2008;Rubin et al, 2009;Bohn, 2010;Haque and Hasking, 2010;Dickson et al, 2011;Thomsen et al, 2011;Gu et al, 2017Gu et al, , 2019 and when adult children recall their parents' lives (Svob and Brown, 2012;Svob et al, 2016;Gu et al, 2019). Transition Theory (Brown et al, 2012(Brown et al, , 2016Brown, 2016Brown, , 2021 contends that these phenomena reflect the degree of change engendered by the transitions in question.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, what is important is how much change has followed in its wake. Consistent with this point, both script-consistent transitions and script-divergent ones are frequently used as temporal landmarks (e.g., Bohn and Habermas, 2016;Shi and Brown, 2016;Gu et al, 2017;Camia et al, 2019) and give rise to a relatively large number of memorable personal experiences (Pillemer et al, 1986(Pillemer et al, , 1988Kurbat et al, 1998;Thomsen and Berntsen, 2005;Uzer and Brown, 2015;Brown et al, 2016;Shi and Brown, 2016;Gu et al, 2017;Thomsen et al, 2021). In addition, both types of events are often mentioned when participants are asked to recall important events from their own lives (Glück and Bluck, 2007;Thomsen and Berntsen, 2008;Rubin et al, 2009;Bohn, 2010;Haque and Hasking, 2010;Dickson et al, 2011;Thomsen et al, 2011;Gu et al, 2017Gu et al, , 2019 and from the lives of their parents (Svob and Brown, 2012;Svob et al, 2016;Gu et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, the LiH effect ranged from 17% to 23.9% for the Bosnian Civil War (1992–1995), 5.5% to 26% for WWII (Bohn & Habermas, 2016 ), 5.3% for the Kosovo War, 13.70% to 26.62% for Lebanese Civil War, and 4.3% for the breakup of Yugoslavia (Brown & Lee, 2010 ; Brown et al, 2009 ) (see Supplementary Table 1 , Online Supplementary Material). Other historical/public events that produced significant LiH effects were the Chinese Cultural Revolutio (11.8–25.9%; Gu et al, 2017 ), earthquake in Turkey (0.3–13.9%; Brown et al, 2009 ), migration to Canada (15%; Shi & Brown, 2016 ), and Fall of Berlin Wall (1.0–7.1%; Camia et al, 2019 ). However, the LiH effect was less apparent in the region where the public events had less impact on the citizens.…”
Section: Theories Of Autobiographical Memory (Am)mentioning
confidence: 99%
“…Camia et al ( 2019 ) administered TIS to the participants recruited from East Germany to assess the impact of the fall of the Berlin Wall. Their results showed that East Germans experienced significantly higher material change but less psychological change.…”
Section: Theories Of Autobiographical Memory (Am)mentioning
confidence: 99%